PUBLIC RELATIONS STRATEGY AND ITS IMPACT ON THE POSITIONING OF INDONESIAN TOURISM INDUSTRY - Iyus Wiadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
The objectives of the research are to acquire findings as follows: a) Description of the existing condition of 5 (five) Indonesian’s tourism destination, i.e.: Bali, Yogyakarta, North and West Sumatera and South Sulawesi; b) Influence of public relations strategy on perception, attitude, and preference of 11 (eleven) tourist generating countries, i.e. USA, England, France, Germany, The Netherland, Japan, Taiwan, South Korea, Malaysia, Singapore, and Australia; c) Prospect tendency on repositioning of the foreign tourist’s perception, attitude, and preference in facing competition with other South East Asian regions tourism destinations. This research uses data based on cross-sectional method using Structural Equation Model (SEM), Multi Dimensional Scaling (MDS) and Trend Analysis. The observation units of the research originate from a sample respondents of 210 foreign tourists from 11 (eleven) tourist generating countries. The number of respondents from each country was taken proportionally. The results of the research are: a) Bali is still the most attractive destination, followed by Yogyakarta, North Sumatra, West Sumatra, and South Sulawesi; b) The Influence of each Public Relations Strategy variable, i.e.: press relations, product publicities, corporate communications, lobbying, counseling, seminars, conferences, publications, events, sponsorships, speeches and news conferences are significant towards perception, attitude and preference of the 11 (eleven) tourist generating countries; and c) Prospect of the Indonesian tourism industry faces a huge opportunity as predicted in the trend of the increase number of foreign tourist visits to Indonesia, since 2006 until 2010. It means that the trend is going to increase continuously provided accompanied by improving as well as implementing of integrated marketing communications strategy, especially in the field of public relations. Specifically it would be much more effective and efficient if those strategically efforts are in alliance and collaborations with other ASEAN regions or countries.